2015
DOI: 10.1089/cmb.2014.0157
|View full text |Cite
|
Sign up to set email alerts
|

WhatsHap: Weighted Haplotype Assembly for Future-Generation Sequencing Reads

Abstract: The human genome is diploid, which requires assigning heterozygous single nucleotide polymorphisms (SNPs) to the two copies of the genome. The resulting haplotypes, lists of SNPs belonging to each copy, are crucial for downstream analyses in population genetics. Currently, statistical approaches, which are oblivious to direct read information, constitute the state-of-the-art. Haplotype assembly, which addresses phasing directly from sequencing reads, suffers from the fact that sequencing reads of the current g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
353
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 380 publications
(370 citation statements)
references
References 35 publications
2
353
0
Order By: Relevance
“…Both tools have been executed on all the instances, but HAPCOL terminated on some of them because no feasible solution existed for that choice of the input parameters. WHATSHAP, which should be able to find a feasible solution for all the instances, computed a solution only for the instances with coverage 15Â and 20Â, while, as expected (Patterson et al, 2015), it was not able to successfully conclude the execution on the instances with coverage 25Â since it exhausted the available memory (256 GB). Table 2 reports, for any combination of input parameters and a, the number of instances with a feasible solution (column 'feas.…”
Section: Simulated Datasetsmentioning
confidence: 64%
See 3 more Smart Citations
“…Both tools have been executed on all the instances, but HAPCOL terminated on some of them because no feasible solution existed for that choice of the input parameters. WHATSHAP, which should be able to find a feasible solution for all the instances, computed a solution only for the instances with coverage 15Â and 20Â, while, as expected (Patterson et al, 2015), it was not able to successfully conclude the execution on the instances with coverage 25Â since it exhausted the available memory (256 GB). Table 2 reports, for any combination of input parameters and a, the number of instances with a feasible solution (column 'feas.…”
Section: Simulated Datasetsmentioning
confidence: 64%
“…We compared HAPCOL with three state-of-the-art haplotyping tools specifically designed for handling long reads, namely, REFHAP, which was shown to be one of the most accurate heuristic methods (Duitama et al, 2012), PROBHAP, a recent probabilistic method which has been shown to be sensibly more accurate than REFHAP (Kuleshov, 2014) and WHATSHAP, the first exact approach for the weighted MEC problem specifically designed for long reads (Patterson et al, 2014(Patterson et al, , 2015. At higher coverages, applications such as SNP calling or validating which SNPs are really heterozygous in the given sample (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the above models and their extended versions are NP-hard (Bafna et al, 2005;Cilibrasi et al, 2007;Duitama et al, 2010), and their exact algorithms run in time exponential in at least one input parameter (Bafna et al, 2005;He et al, 2010;Xie et al, 2010bXie et al, , 2008Wang et al, 2010;Bonizzoni et al, 2015;Patterson et al, 2015;Pirola et al, 2015). Therefore, a large number of heuristic algorithms have been designed to deal with the problem (Panconesi and Sozio, 2004;Wang et al, 2005;Genovese et al, 2008;Duitama et al, 2010;Xie et al, 2012).…”
mentioning
confidence: 99%